Whole-Foods, Plant-Based Diet Alleviates the Symptoms of Osteoarthritis. (28th February 2015) - Clinton, Chelsea M.; O'Brien, Shanley; Law, Junwen; Renier, Colleen M.; Wendt, Mary R.
Abstract : Objective . To evaluate the effectiveness of a whole-foods, plant-based diet (WFPB) to reduce symptoms of osteoarthritis. Methods . Six-week, prospective randomized open-label study of patients aged 19–70 with osteoarthritis. Participants were randomized to a WFPB (intervention) or continuing current diet (control). Outcomes were assessed by mixed models analysis of participant self-assessed weekly SF-36v2 domain t scores, weekly Patient Global Impression of Change (PGIC) scales, and mean weekly Visual Analog Scale (VAS) pain assessment. Mixed models analysis also evaluated pre-post change from baseline level for standard clinical measures: weight, BMI, body temperature, pulse, and blood pressure. Results . Forty participants were randomized. Thirty-seven of them, 18 control and 19 intervention, completed the study. The intervention group reported a significantly greater improvement than the control group in SF-36v2 energy/vitality, physical functioning, role physical, and the physical component summary scale. The differences between the intervention and control PGIC scales were statistically significant over time. Intervention group improvement in VAS weekly mean was also significantly greater than that of the control group from week 2 onward. Conclusion . Study results suggest that a whole-foods, plant-based diet significantly improves self-assessed measures of functional status among osteoarthritis patients.